1983
DOI: 10.1177/154193128302700505
|View full text |Cite
|
Sign up to set email alerts
|

Speed-Accuracy Tradeoffs in Spatial Orientation Information Processing

Abstract: A study was conducted to further evaluate the Manikin Task, a test of spatial orientation information processing.The objectives of the study were to determine the speed vs. accuracy tradeoff .characteristics of the task and to assess performance on the task under the influence of ethyl alcohol. Response times and accuracy were measured on five subjects over a five-week weriod. Analysis of the data indicated a definite decline in accuracy corresponding to a forced decrease in response time. The effect of alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…Across modalities and categories, we found that adults have more efficient information processing than children. Adults' higher evidence accumulation compared to children is similar to prior work in other tasks (Manning et al, 2021;Nordmeyer et al, 2016;Ratcliff et al, 2012;Schneider & Frank, 2016). This finding also complements prior work in adults, where evidence accumulation rates are associated with individual differences in working memory abilities (Ester et al, 2014).…”
Section: Adults Learned Better Than Children Even When Controlling Fo...supporting
confidence: 80%
See 1 more Smart Citation
“…Across modalities and categories, we found that adults have more efficient information processing than children. Adults' higher evidence accumulation compared to children is similar to prior work in other tasks (Manning et al, 2021;Nordmeyer et al, 2016;Ratcliff et al, 2012;Schneider & Frank, 2016). This finding also complements prior work in adults, where evidence accumulation rates are associated with individual differences in working memory abilities (Ester et al, 2014).…”
Section: Adults Learned Better Than Children Even When Controlling Fo...supporting
confidence: 80%
“…Prior work has generally demonstrated that children have more cautious responses than adults (Manning et al, 2021;Nordmeyer et al, 2016;Ratcliff et al, 2012;Schneider & Frank, 2016), though in some tasks children make more impulsive, less cautious decisions than adults (Martinez et al, 2018). Here, we found that, in general, children had less cautious responses than adults and that children had more similar decision thresholds for correct and incorrect responses.…”
Section: Asymmetric Development Across Categories and Modalitiessupporting
confidence: 44%
“…The two tests selected to exercise this paradigm are the Manikin test and the Mathematical Processing test. The Manikin test has a long history of use (Benson and Gedye, 1963;Reader, Benel, and Rahe, 1981;Schlegel and Storm, 1983) and is presented in a wide variety of formats by military psychologists (Miller, Takamoto, Bartel, and Brown, 1985). As implemented in this experiment, a manikin "stick figure" is presented facing either forward or backward.…”
Section: B2mentioning
confidence: 99%
“…Manikin Task (MAN). This task has had a long history of use (Benson & Gedye, 1963;Reader, Benel, & Rahe, 1981;Schlegel & Storm, 1983) and has been presented in a wide variety of formats by military psychologists (Miller, Takamoto, Bartel, & Brown, 1985). As implemented in this experiment, a manikin "stick figure" is presented facing either forward or backward.…”
Section: Dual Task -Tracking and Sternberg Memorymentioning
confidence: 99%